Dissociative symptoms are associated with reduced neuropsychological performance in patients with recurrent depression and a history of trauma exposure - Parlar, Melissa (Eur J Psychotraumatol, 2016)
BACKGROUND: Although preliminary work suggests that dissociative symptoms may impact neuropsychological performance in trauma-exposed populations, the relation between dissociation and cognitive performance has not been explored in patients with depression. OBJECTIVE: The present study examined dissociative symptoms in relation to neuropsychological performance in participants with a primary diagnosis of recurrent major depressive disorder (MDD) and a history of trauma exposure. METHOD: Twenty-three participants with MDD and 20 healthy controls who did not differ in age, sex, education, or IQ were assessed. In addition to a standardized neuropsychological battery assessing frontotemporally mediated cognitive processes, participants completed clinical measures assessing dissociative symptoms, illness severity, and past history of trauma exposure. RESULTS: Among participants with MDD, greater severity of derealization was associated with reduced performance on measures of delayed visuospatial recall and recognition on a task of verbal memory recognition. In addition, more severe depersonalization was associated with slower processing speed and a response style lending itself toward better performance in a less active environment. CONCLUSIONS: These findings point toward dissociative symptoms as a transdiagnostic factor associated with neuropsychological dysfunction in patients with depression and a history of trauma. Limitations and recommendations for future research are discussed.